Distribution of important medicinal plant species in Nepal under past, present, and future climatic conditions - Kunwar, Ripu M.; Thapa-Magar, Khum B.; Subedi, Suresh C.; Kutal, Durga H.; Baral, Bikash; Joshi, Nabin R.; Adhikari, Binaya; Upadhyaya, Kul S.; Thapa-Magar, Santosh; Ansari, Abdul S.; Thapa, Gokarna J.; Bhandari, Ananta R. (Ecological indicators, 2023)
•Total 1041 presence points of seven species were used for ensemble species distribution modeling.•Modeling carried out using Shared Socioeconomic Pathways 2–4.5 and 5–8.5 for years 2050 and 2070.•Elevation, BIO2, BIO7, BIO18 and BIO19 were found as important for determining distribution of medicinal plants.•The range of alpine species was projected to be increased in central mountains.•Future habitats of (sub)tropical and temperate species were found to be constrained. Climate change is causing shifts in the habitat, distribution, ecology, and phenology of Himalayan plants. These changes are predicted to continue, jeopardizing the survival of medicinal plant species and local livelihoods that rely on them. We analyzed the present and future diversity and distribution of medicinal plant species influenced by different climate change scenarios, and calculated the climatic niche of the species using ensemble species distribution modeling (eSDM). We compiled 1041 (N) geospatial data of seven high-value medicinal plant species of Nepal: Aconitum spicatum (n = 100), Allium wallichii (n = 151), Bergenia ciliata (n = 48), Nardostachys jatamansi (n = 121), Neopicrorhiza scrophulariiflora (n = 94), Paris polyphylla (n = 310) and Valeriana jatamansi (n = 217) including over 85 % from field surveys and the rest from literature and online database. We used bioclimatic variables from Models for Interdisciplinary Research on Climate (MIROC) of version MIROC6, and selected Shared Socioeconomic Pathways (SSP)2-4.5 and SSP5-8.5 for the year of 2050 and 2070 for modeling. We found elevation, mean diurnal and annual temperature ranges (BIO2 and BIO7), and precipitation of warmest and coldest quarters (BIO18 and BIO19) to be the most high weight cofactors for projecting the future potential distribution of high-value medicinal plants in Nepal. Results showed that the suitable range of distribution for high-value medicinal plants would increase and concentrate in mountainous areas of central Nepal, but decline in (sub)tropical and temperate areas, suggesting both in-situ and ex-situ conservation practices, respectively.